Upaya Guru Pendidikan Agama Islam dalam Mengatasi Penyimpangan Perilaku Siswa di SMPN 03 Padang Panjang - Mutiara Iqlima; Taufik Rahman; Zulfikri Zulfikri (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Teachers hold a crucial responsibility in every stage of students' development, including intellectual and spiritual growth. This role is vital in fostering students' emotional maturity, enabling them to adapt to changes and advancements in their environment. This study aims to explore the efforts of Islamic Religious Education (IRE) teachers in addressing behavioral deviations among students at SMP Negeri 03 Padang Panjang. The research employs a descriptive qualitative method by gathering information through interviews, observations, personal documents, notes, and other relevant materials. The identified forms of student behavioral deviations at SMP Negeri 03 Padang Panjang include smoking, bullying, lack of attention and concern toward teachers during lessons, failure to complete assignments, disrespectful behavior and lack of politeness, absence from congregational prayers, bringing mobile phones to school without permission, skipping classes, and using inappropriate language.